Uniform Crime Reporting Program Data (United States): Property Stolen and Recovered, 2001 ([Verlag nicht ermittelbar], 2003)
Since 1930, the Federal Bureau of Investigation has compiled the Uniform Crime Reports (UCR) to serve as periodic nationwide assessments of reported crimes not available elsewhere in the criminal justice system. Law enforcement agencies contribute reports either directly or through their state reporting programs. Each year, this information is reported in four types of files: (1) Offenses Known and Clearances by Arrest, (2) Property Stolen and Recovered, (3) Supplementary Homicide Reports (SHR), and (4) Police Employee (LEOKA) Data. The Property Stolen and Recovered data are collected on a monthly basis by all UCR contributing agencies. These data, aggregated at the agency level, report on the nature of the crime, the monetary value of the property stolen, and the type of property stolen. Similar information regarding recovered property is also included in the data.